2012
DOI: 10.1128/aac.00110-12
|View full text |Cite
|
Sign up to set email alerts
|

Use of Carbapenems against Clinical, Nontyphoid Salmonella Isolates: Results from In Vitro and In Vivo Animal Studies

Abstract: fThe emergence of multidrug-resistant Salmonella isolates has created the need for new therapeutic agents. We evaluated the intracellular activity of four carbapenem compounds against clinical nontyphoid Salmonella (NTS) isolates in vitro and ex vivo. Subsequently, the efficacy of carbapenem treatment against selected Salmonella isolates in vivo was assessed using a murine peritonitis model. The MIC 50 and MIC 90 for doripenem, ertapenem, imipenem, and meropenem against 126 NTS isolates were found to be 0.062 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…High sensitivity to chloramphenicol was similar to that of Elmadiena et al who also found majority of their Salmonella isolates sensitive to chloramphenicol [48] . Also, high susceptibility of isolates to meropenem was in agreement to results of Tang et al who found meropenem a good therapeutic option in testing various multidrug resistant Salmonella isolates [49] .…”
Section: Discussionsupporting
confidence: 77%
“…High sensitivity to chloramphenicol was similar to that of Elmadiena et al who also found majority of their Salmonella isolates sensitive to chloramphenicol [48] . Also, high susceptibility of isolates to meropenem was in agreement to results of Tang et al who found meropenem a good therapeutic option in testing various multidrug resistant Salmonella isolates [49] .…”
Section: Discussionsupporting
confidence: 77%
“…Many experimental models have been developed to study Salmonella infections including various in vitro, ex vivo , and in vivo models (Table 1 ). The most commonly used ones are the two-dimensional (2-D) immortalized cell line models including the Caucasian colon adenocarcinoma (Caco2) cells (Martinez-Argudo and Jepson, 2008 ), the immature human normal fetal intestinal epithelial cells (H4) (Newburg et al, 2016 ), the mature human metastatic colonic epithelial cells (T84) (Newburg et al, 2016 ), the human normal colon mucosal epithelial cells (NCM-460) (Newburg et al, 2016 ), the Microfold cells (or M cells) (Martinez-Argudo and Jepson, 2008 ), the RAW 264.7 murine macrophage cells (Tang et al, 2012 ), the cervical cancer (HeLa) cells (Fang et al, 2017 ), and the gut fermentation models (Le Blay et al, 2009 ). In addition, three-dimensional (3-D) organotypic models derived from the Int-407 cell line (later found to be a HeLa derivative) and the human colorectal adenocarcinoma cells (HT-29) (Nickerson et al, 2001 ; Höner Zu Bentrup et al, 2006 ).…”
Section: Current Models For Studying Salmonellamentioning
confidence: 99%